Paid vs. Organic in Sustainability Performance: Which Approach Delivers Greater Long-Term Value? - Reztrianti, Diajeng; Abdullah, Muhamad Al Faruq; Juanna, Andi; Ferry, Setyo; Wibowo (Applied Business and Administration Journal, 2025)
Digital transformation has driven fundamental changes in marketing practices, compelling companies to shift their focus beyond economic gain toward broader sustainability goals. Paid advertising and organic reach represent two primary approaches in digital marketing, each with distinct strategic advantages. The objective of this study is to compare the effectiveness of these two approaches in supporting sustainability performance, while also exploring the potential for their integration into a sustainability-oriented hybrid strategy. Employing a Systematic Literature Review (SLR) method based on the PRISMA 2020 protocol, a total of 20 articles were selected and analysed from Scopus-indexed databases. The findings indicate that paid advertising is highly effective in achieving rapid reach and initial conversions, while organic reach is more effective in fostering long-term engagement and customer loyalty. The hybrid strategy is shown to be the optimal approach, combining the strengths of both methods in a synergistic manner. The present study makes a conceptual contribution to the field of sustainable digital marketing by offering a novel framework for industry practitioners to design strategies that balance operational efficiency with long-term sustainability objectives.